A current clinical overview of atrophic gastritis. (1st February 2020) - Annibale, Bruno; Esposito, Gianluca; Lahner, Edith
ABSTRACT: Introduction : Atrophic gastritis (AG) is a complex syndrome which arises as a consequence of H. pylori infection or in the context of gastric autoimmunity. It often deserves a benign course but may lead to potentially life-threatening complications: cancer and anemia. This review aims to address traditional and innovative knowledge on this often under-diagnosed disorder. Areas covered : This review covers clinical presentation, risk factors, diagnosis, and management of AG and provides an updated resource for clinicians to get insight into this challenging disorder. Updated literature was searched in PubMed. Manual search from reference lists of publications was performed. Expert opinion : A case-finding strategy may be beneficial in individuals with anemia, dyspepsia, autoimmune thyropaties and type 1 diabetes, and family history of gastric cancer. AG is linked to gastric cancer risk and endoscopic surveillance is indicated according to topography of gastric atrophy and risk factors. The direction for future research in AG is summarized.